Effect of silage and soybean straw based Total Mixed Ration (TMR) on the growth performances of growing bull calves (Bangladesh Journal of Livestock Research, 2020)
This study was undertaken to know the effect of silage and soybean straw based Total Mixed Ration (TMR) on the growth performances of growing bull calves. 30 growing bull calves were divided into 5 treatment groups considering their initial body weight 111.30±6.67 to115.66±10.69 kg and age 24 to 26 months, respectively. Five types of TMR were prepared with different roughage and concentrate ratios (R: C) as T1=70:30, T2=60:40, T3=50:50, T4=40:60, T5=30:70. TMR intake, DM intake, CP intake of animals in T2 group was significantly (P